APLIKASI PENCARIAN LOKASI KULINER DAN WISATA DI KOTA JAMBI DENGAN SISTEM INFORMASI GEOGRAFIS BERBASIS ANDROID: Android, Culinary, Google Maps API, Geographic Information System, Jambi , Smartphone, SQLite - Puspitorini, Sukma; Wahyuning Astuti, Reny; Munandar, Aris (JURNAL AKADEMIKA, 2018)
Jambi City is one of the cities in Jambi Province, and also the seventh largest city on the island of Sumatra. This city has some unique culture, tourism and culinary that are the hallmarks of Jambi city which can be an attraction for domestic and foreign tourists. During this time tourists and culinary lovers in seeking information or getting information from Wikipedia or personal web that has a limited reference. For domestic and outside tourists, this method is less effective because it will spend a lot of time. The purpose of this study is to build a geographic information system application that can help people and tourists to find culinary and tourist places in Jambi City. This application is built on the Android platform so that it can be accessed by users via their smartphone anywhere and anytime. The application was built using the Java programming language with SQLite database and integrated with the Google Maps API as navigation to find out the map of the location of the culinary and tourist destinations sought. In this application, users can find out information on places, menus, prices, and locations of culinary and tourist attractions, the history of Jambi City and its distinctive products. The results of this study, users can search the location of culinary and tourist places in the city of Jambi more quickly with complete and detailed information.